Growth of garment industry in Bangladesh : economic and social dimensions ; proceedings of a National Seminar on Ready-Made Garment Industry, held in Dhaka, Bangladesh, January 21 - 22, 2000 - 9 (Dhaka : Community Development Library, 2001)
Contributed articles; most relating to the post-1971 period.
Includes bibliographical references.
jakir
Keywords: Bangladesh -- History